2013
DOI: 10.1504/ijbe.2013.050633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of network market orientation on new ventures' international performance

Abstract: By combining international entrepreneurship and marketing aspects, this work attempts to emphasise the importance of relational knowledge in international new ventures by studying the influence of network market orientation on the international results obtained by these firms. The results obtained in the comparison with the proposed structural equations model confirm that network market orientation is a determining factor for firms to achieve better international results. This influence is observed both direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 117 publications
(226 reference statements)
0
10
0
Order By: Relevance
“…Hypothesis H1: Market orientation has a direct positive effect on innovation performance of SMEs, was therefore accepted. This implies that when SMEs become market-orientedby being customer-oriented (focusing on the needs and wants of customers), understanding its competitors, and having effective coordination within the various functions of the firm -, they have more chance of enhancing their innovation performance (Monferrer et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothesis H1: Market orientation has a direct positive effect on innovation performance of SMEs, was therefore accepted. This implies that when SMEs become market-orientedby being customer-oriented (focusing on the needs and wants of customers), understanding its competitors, and having effective coordination within the various functions of the firm -, they have more chance of enhancing their innovation performance (Monferrer et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The literature generally agrees that a market-oriented company positively impacts overall success (Atuahene-Gima, 1995;Baker & Sinkula, 2005;Laforet, 2009) and innovation (Jimenez-Jimenez et al, 2008). This is most likely because they can meet the expectations of their customers while also absorbing new knowledge, which can be used to inspire innovation (Monferrer et al, 2013;Jaworski & Kohli, 1993). Verhees and Muelenberg (2004) found that highly innovative businesses exhibit constraints that inhibit product innovation, whereas lees innovative businesses contribute to its creation.…”
Section: Market Orientation and Innovation Performancementioning
confidence: 99%
“…In this respect, this study covers the mutually complementary nature of both factors in a single construct known as network market orientation (NMO). Thus, although previous studies have emphasised the importance of MO in the context of relationships between firms, they have not analysed it as an inter-business phenomenon in itself, but rather as the sum of the market orientations of the various individual firms [22,37,39,40]. The present work analyses the role of NMO differently, understanding it as an orientation established jointly by the different members making up the network.…”
Section: Introductionmentioning
confidence: 94%
“…Some researchers have argued that the network embeddedness (the strength of network ties) is a determining factor for internalization of firms seeking a cooperation network with international partners [13,51]. For instance, Monferrer [5] found empirical support for the effects of a network on international performance or sustainable competiveness by examining new international ventures, thus discovering the direct and indirect mediating effect of a network on differentiation-and cost-based competitive advantage-and confirming that a network is an important factor in improving international performance. In a study of 155 Czech SMEs, Musteen [52] found that an international network plays an important role in accelerating internationalization and improving international performance.…”
Section: International Network Embeddedness and International Performancementioning
confidence: 99%
“…Essentially, SMEs have turned to international markets to overcome the difficulty of maintaining and expanding their domestic market share [4]. These companies especially seek niche strategies, and their success might depend on their ability to enter international markets [5]. SMEs use networks to cope with their inherent limitations, such as lack of resources [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%